A Dynamic Analysis of BLDC Motor by Using Matlab/Simulink and Mathematica - (:unkn) unknown (IEEE, 2017)
This paper studies the dynamic performance of BLDC motor with MatLab/Simulink, and the results of torques and speeds are verified with Mathematica software. MatLab/Simulink provides suitable environment for control application and power electronic design, whereas Mathematica is better for symbolic part and therefore it could be preferred for design and control applications for electrical motors. By integrating these programs' features provides a better dynamic analysis when predicting the precise value of torque and speed, determined by waveforms of back-emf. The simulation results show that verifying the performance of BLDC motor with Mathematica software gives the more accurate values in current, torque and speed calculations.
Keywords: MatLab; Mathematica; Brushless Direct Current Motor; Back Electro Motive Force; Hall Effect Sensors; TORQUE